Media (il)literacy an evaluation of the curriculum and implementation of the Department of Education's special program in journalism - Torres, Sarah Isabelle S.; Arao, Danilo A.; University of the Philippines. College of Mass Communication (2014)
"This study evaluated the curriculum and implementation of the Special Program in Journalism (SPJ). By conducting surveys, focus group discussions, and interviews and by analyzing the school publication of five national high schools, the researcher found out that SPJ is ineffective in instilling media literacy to the students. Media Literacy will help the students understand how media operates, thus, they will be able to produce outputs that are socially relevant, critical, and in-depth. For one, the curriculum includes lessons and activities that are mostly technical in nature. There are no theoretical topics such as ethics, history of the press, or media ownership. Second, most of the SPJ teachers have little background on Journalism and they are not trained enough to teach the program effectively. Third, most of the students are not really inclined in Journalism and do not see themselves as media practitioners in the future. Lastly, the Department of Education's budget for the program is far from what the curriculum needs. All of these lead to the low Media Literacy levels of the students, SPJ, therefore, has to be re-evaluated and amended. In conclusion, Media Literacy should be added in the curriculum so the students will not only be equipped with technical skills but with theoretical knowledge, as well."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Philippines. Department of Education; Media literacy -- Philippines; Media literacy -- Study and teaching -- Philippines; Journalism -- Study and teaching -- Philippines; Curriculum evaluation